Hydroclimatic extremes threaten groundwater quality and stability - Simon A. Schroeter; Alice May Orme; Katharina Lehmann; Robert Lehmann; Narendrakumar M. Chaudhari; Kirsten Küsel; He Wang; Anke Hildebrandt; Kai Uwe Totsche; Susan Trumbore; Gerd Gleixner (Nature Communications)
Abstract Heavy precipitation, drought, and other hydroclimatic extremes occur more frequently than in the past climate reference period (1961–1990). Given their strong effect on groundwater recharge dynamics, these phenomena increase the vulnerability of groundwater quantity and quality. Over the course of the past decade, we have documented changes in the composition of dissolved organic matter in groundwater. We show that fractions of ingressing surface-derived organic molecules increased significantly as groundwater levels declined, whereas concentrations of dissolved organic carbon remained constant. Molecular composition changeover was accelerated following 2018’s extreme summer drought. These findings demonstrate that hydroclimatic extremes promote rapid transport between surface ecosystems and groundwaters, thereby enabling xenobiotic substances to evade microbial processing, accrue in greater abundance in groundwater, and potentially compromise the safe nature of these potable water sources. Groundwater quality is far more vulnerable to the impact of recent climate anomalies than is currently recognized, and the molecular composition of dissolved organic matter can be used as a comprehensive indicator for groundwater quality deterioration.